ANIMASI KETINTING SURYA SEBAGAI FILM EDUKASI PEMANFAATAN ENERGI DI WILAYAH KALIMANTAN UTARA - Suprianto Suprianto; Devita Sekar Arum; Adisa Dewi Yudiwardhani; Fitria Khairun Nisa; Muhammad Muhammad (LPPM Unbaja, 2024)
Short animated film inspired by the surrounding environment in North Kalimantan which often uses boats called outboard motorboats or ketinting boats as a means of river transportation. Ketinting is a type of traditional boat that uses a motor propeller and is placed at the back in a position immersed in the water as a driving force to run the boat using diesel fuel, and is often found in various areas, especially the North Kalimantan region. Ketinting boats are usually used as a means of transportation to move places via river routes, and are usually also used by fishermen as transportation to find income in the form of fish. This animation tells the story of the life of a computer student who has parents who work as fishermen. This animation tells the problem of how difficult and expensive it is to get diesel fuel and then the students find a solution by using technology that uses solar energy as a substitute for diesel fuel. The animation creation process consists of pre-production, production and post-production using dialogue and music as support. The results of the animated video are created as a medium for entertainment, information and education related to solar energy that can be watched by all groups.